Review strategi penyelesaian konflik sosial atas tanah: studi kasus konflik antara komunitas Ketajek dengan perusahaan daerah perkebunan Jember, di Kecamatan Panti, Kabupaten Jember, propinsi Jawa Timur - Suporahardjo (Universitas Indonesia, 2004)
The land disputed by Ketajek community and Jember Estate company (PDP) used to belong to the rights of Erfpach Verponding No. 2712 and No. 2713 They are known as Ketajek Estate I and II, on behalf of NV. Land Bow My Oud Djember (LMOD), with the overall area of 477.87 hectares located in Pakis and Suci villages, kecamatan Panti, Kabupaten Jember, East Java. The rights ended on 29 July 1967. The land conflict broke out in 1972 when the local government under Bupati Abdul Hadi, who was also one of PDP’s board of directors, planned to take over Ketajek Estate I and II which had long been cultivated by Ketajek local people since 1950s. Ketajek I and II having been distributed since 1964 by means of landreform policy, the take-over has caused an intractable conflict—up to now. This research tries to explore how the social conflict of Ketajek land remains unresolved, and what kinds of conflict resolution strategies have been adopted by the conflicting parties as well as those involved in the turbulence of conflict. So, the objectives of this research are: 1) to dig up and map the history and sources of conflict; 2) to identify the factors influencing the conflict escalation; 3) to observe the process of selection and the result of conflict management/resolution strategy applied by the conflicting parties; and 4) to provide a recommendation of how to improve the existing conflict resolution methods between Ketajek community and PDP Jember. The research made use of qualitative approach. This approach best-matched with the objectives of the research, i.e. to understand conflict fenomena in connexion with the presence of multi parties, both those in favor and those against the resolution of the land conflict between Ketajek community and PDP Jember. For the pros and cons, interviews were given to get a deep understanding of what opinions they have about the resolution proposed for Ketajek land conflict. Ideas obtained from the interviews with informants and data from scrutinizing the documents about intervention methods for this conflict were collected to be reviewed and analyzed to get the strength and weaknesses by comparing with experience from other sites or with the preceding cases. In this research, conflict was seen as a form of interaction which can develop, integrate, and continue the structures within a society. It is understood from both positive and negative perspectives because conflict should be faced and managed as it can be understood from the perspectives of the parties involved, from the very cause, from the stages of development, from the factors influencing the escalation and from the possibilities of intervention mechanisms. The important findings of the research are, among others, five methods of resolution proposed by interest parties, i.e.: 1) providing a compensation; 2) bringing the case to the court; 3) taking an extra-court law (nonlitigation) or a political action; 4) building dialog/negotiation; and 5) building a partnership between PDP and Ketajek local people. The local government/PDP jember prefers options 1 and 2, whereas Ketajek community prefers points 3 and 4. From the analysis of the above failure, it was found that: the options were made unilaterally by the power-ed party, and it failed to hit the source of the problems, the facilitators/mediators were unskilled, the analysis of the shared problems was poor, dialogs between conflicting parties were frequently confrontational, the processes were more confrontational than collaborative, groups of Ketajek community were polarized, there was a rivalry between interest parties that went with the community, there was a lack of political will from elites in the local government/PDP, DPRD to share power/activities/benefit with the local community over the natural resources. The conclusion is that the five resolutions failed to lead to an agreement supported by all parties and failed to satisfy all. From the perspective of Jember local government’s policy, it can be concluded that the local government did not have adequate infrastructures, either in the form of institutions or human resources to enact a nonlitigation conflict resolution or alternative dispute resolution (ADR). To manifest the ADR was all in theory; in practice, none of the policies used it Considering the ideas proposed by interest parties in the Ketajek land conflict, therefore, it is recommended to the local government and DPRD Jember to think over collaborative strategies to resolve Ketajek land conflict. In plying the collaborative strategies, the conflicting parties must have a will to shift from adversarial approaches to nonadversarial ones since the collaborative processes need openness, respect for difference, the awareness of interdependency, active participation of the conflicting parties, way out and agreed relationship, and the awareness that collaboration is a process, not a recipe. There are four general designs for collaboration to be noted carefully by the conflicting parties related to joint efforts to make the smart choice of: 1) appreciative planning; 2) collective strategy; 3) dialog; and 4) negotiation of resolution. In order to be able to build a constructive design for collaboration that all conflicting parties are committed to, there must be clear stages for a common guideline. The stages should at least comprise first stage, a clear problem statement; second stage, a clear direction of collaboration; and third stage, a clear operation. To support a successful collaborative strategy, the support from Jember local government is an important factor. Without a strong will from the local government to sustain it, it is impossible for the collaborative processes to be operated. Therefore, the political will of the local government should not only be typed on POLDAS text, but should also be realized in practice, by providing skilled human resources for the best facilitators/mediators and giving support or developing the institution.